C1D family proteins in coordinating RNA processing, chromosome condensation and DNA damage response. Issue 1 (March 2016) - Jackson, Rebecca; Wu, Jocelyn; Chen, Ee
Abstract Research on the involvement of C1D and its yeast homologues Rrp47 (S. cerevisiae ) and Cti1 (S. pombe ) in DNA damage repair and RNA processing has remained mutually exclusive, with most studies predominantly concentrating on Rrp47. This review will look to reconcile the functions of these proteins in their involvement with the RNA exosome, in the regulation of chromatin architecture, and in the repair of DNA double-strand breaks, focusing on non-homologous end joining and homologous recombination. We propose that C1D is situated in a central position to maintain genomic stability at highly transcribed gene loci by coordinating these processes through the timely recruitment of relevant regulatory factors. In the event that the damage is beyond repair, C1D induces apoptosis in a p53-dependent manner.